Radiation effect of M-slot patch antenna for wireless application - Yousif Allbadi; Huda Ibrahim Hamd; Ilham H. Qaddoori (Institute of Advanced Engineering and Science, 2022)
Today, the specific absorption rate has become an important and necessary measurement when designing and implementing any type of antenna. In recent years, various devices have appeared that use different frequencies for wireless communication systems, which are a source of electromagnetic radiation. The M-slot antenna is designed in this paper to operate in multi-band frequencies for wireless communications using computer simulation technology (CST) software 2020. The radiation effect for this antenna is calculated for tissue mass of the human fingertips, which consists of three layers (skin, meat, and bone), over a mass of 1 g and 10 g according to the IEEE and International Commission on Non-Ionizing Radiation Protection (ICNIRP) organization. The results are shown three applications in the communication system, which are Wi-Fi, worldwide interoperability for microwave access (Wi-Max) and, satellite X-band and, the value of specific absorption rate (SAR) increase with increased frequency.